The Effect of Single-Parent Parenting, Peer Conformity, and Self-Concept on Adolescent Religiosity - Rina Setyaningsih; Nyayu Khodijah; Munir Munir (STAI Hubbulwathan Duri, 2021)
The study aimed to prove the effect of single-parent (father) parenting and peer conformity on religiosity in adolescents in the Marga Sekampung sub-district, East Lampung district. The study was a quantitative study with a population and sample of 51 adolescents aged 10-16 years. Data was collected through questionnaires and documentation. Instrument validity was through Product Moment correlation and instrument reliability through the split-half technique. The data analysis technique is through the prerequisite test with normality and homogeneity tests, variable description, and the hypothesis test with simple linear regression and multiple regression tests. The study found that the effect of single-parent (father) parenting, peer conformity, and self-concept together on adolescent religiosity was 82.8% and 17.2% affected by other factors.